2022
DOI: 10.21203/rs.3.rs-1263582/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female Education and Maternal Health Care Utilization: Evidence from Uganda

Abstract: Background: Maternal health care Indicator Is among the key Indicators of population health, health economic development. Therefore, the study attempts to explore female education and maternal healthcare utilization in Uganda. The study identifies the causal effect of introduction of free education, by exploiting the age as an instrument at the second stage model. This instrument provides an exogenous source of variation in the years of schooling and allows to implement a regression discontinuity design, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Saxena et al (2013) highlighted that education improves pregnant women's behavior and attitude toward maternal health care services. Several study results suggested that higher educational attainment increases seeking healthcare behavior and attitude among women (Amwonya et al, 2022;Saxena et al, 2013). Moreover, Kaffenberger and Pritchett (2021) used the Demographic Health Survey data from 54 countries, and they found in a cross-tabulation that child mortality gap was 11.5% between educated women (20.9% experience death of a child) and uneducated women (32.4% experience death of a child).…”
Section: Benefits Of Education For Allmentioning
confidence: 99%
“…Saxena et al (2013) highlighted that education improves pregnant women's behavior and attitude toward maternal health care services. Several study results suggested that higher educational attainment increases seeking healthcare behavior and attitude among women (Amwonya et al, 2022;Saxena et al, 2013). Moreover, Kaffenberger and Pritchett (2021) used the Demographic Health Survey data from 54 countries, and they found in a cross-tabulation that child mortality gap was 11.5% between educated women (20.9% experience death of a child) and uneducated women (32.4% experience death of a child).…”
Section: Benefits Of Education For Allmentioning
confidence: 99%